THE ROLE OF A PRACTICAL PSYCHOLOGIST IN THE FORMATION OF ENVIRONMENTAL AWARENESS OF PROFESSIONAL EDUCATION STUDENTS (Innovative professional education, 2023)
Aspects of the formation of environmental awareness of vocational education students through the prism of the ecological needs of modern Ukraine are considered. The role of a practical psychologist of a professional education institution in the process of forming the environmental consciousness of future specialists is determined.
Keywords: environmental awareness, practical psychologist of a vocational education institution, vocational education students